L' évangile en Flandre - Henry, René (Bruxelles : Oscar Schepens, 1903)
Bibliotheek Camille Huysmans
Dedicator: Henry, René, dedicatee: Huysmans, Camille
Overdruk uit: La Revue Générale, september 1903
Frans
Brochure
Keywords: cultuur; religie; Vlaanderen